Bahan Ajar Membaca Permulaan dengan Menggunakan Media Fabel di Kelas Awal Integrasi Teknologi Informasi dalam Pembelajaran Anak Usia Dini - Reni Gustiwati Z (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The writing of this article aimed to describe the conceptual discussion of the theory of teaching reading materials by using fable media that can be used in the initial class. This article discussed theories about teaching materials, preliminary reading, and fable media for early classes. This study applied literature review method which collected the related information from several relevant references. Teaching materials were a set of materials systematically arranged to be used in the learning process. Teaching material was a book that contains a scientific analysis of the curriculum in written form. In the meantime, fable media was a fairytale literature that displays the character and characteristics of humans in animal figures. Based on the discussion of the existing theories in the article, it can be concluded that the initial reading material using fable media can be used in the early class because it can make students master good and bad characters found in the fable story.